2019
DOI: 10.1093/eurpub/ckz167
|View full text |Cite
|
Sign up to set email alerts
|

Ethical aspects of digital health from a justice point of view

Abstract: Digital health is transforming healthcare systems worldwide. It promises benefits for population health but might also lead to health inequities. From an ethical perspective, it is hence much needed to adopt a fair approach. This article aims at outlining chances and challenges from an ethical perspective, focusing especially on the dimension of justice—a value, which has been described as the core value for public health. Analysed through the lenses of a standard approach for health justice—Norman Daniels’ ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
30

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 17 publications
0
79
0
30
Order By: Relevance
“…Health care providers are recommended to play an important role in providing support to those patients who have low eHealth literacy and thus need support in navigating among often-conflicting health information available on the Internet [59]. From an ethical perspective, it is crucial that all stakeholders, especially those delivering eHealth solutions, design interventions in an ethical and fair way, fostering health equity for all population groups and taking into account the needs of disadvantaged groups [20]. To end, for all of them left outside the digital society today and/or in the future, it is of great importance to create solutions making it possible for them to take advantage of the benefits of EICT solutions in society, including eHealth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health care providers are recommended to play an important role in providing support to those patients who have low eHealth literacy and thus need support in navigating among often-conflicting health information available on the Internet [59]. From an ethical perspective, it is crucial that all stakeholders, especially those delivering eHealth solutions, design interventions in an ethical and fair way, fostering health equity for all population groups and taking into account the needs of disadvantaged groups [20]. To end, for all of them left outside the digital society today and/or in the future, it is of great importance to create solutions making it possible for them to take advantage of the benefits of EICT solutions in society, including eHealth.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with an increasing and aging global population [17], there is a lack of health care professionals [18] generating substantial challenges in health care [19]. Digital solutions are transforming health care worldwide [20] and eHealth services and functions are emphasized to play a crucial role in solving these challenges [21][22][23]. The concept of eHealth has several definitions [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also scope for intentional discrimination 22 . The US investigative journalism organization ProPublica demonstrated that they could restrict advertisements on Facebook for attractive rental properties in New York to exclude African–Americans, Jews and anyone who had shown an interest in aids for disabled people 23 .…”
Section: Five Concerns About Digitalizationmentioning
confidence: 99%
“…Digital services in eldercare are rapidly becoming more common, which shows that technology affects human practices and experiences [20][21][22], and, therefore, ethical decision-making [23]. The digital transition in eldercare is already taking place and, as research publications on the ethics of digital care are still scarce, this article investigates how technology affects the ethical decision making of eldercare professionals and what, if anything, makes that decision making difficult [24].…”
Section: Introductionmentioning
confidence: 99%